Engineering equality an essay on European anti-discrimination law - Somek, Alexander (Oxford : Oxford University Press, 2011)
Examining the rise of European anti-discrimination law, this book provides a critique of the focus on and implementation of anti-discrimination law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Discrimination -- Law and legislation -- European Union countries; European Union countries -- Social policy